HUBUNGAN TINGKAT PENGETAHUAN TENTANG KANKER LARING TERHADAP SIKAP DAN PERILAKU MEROKOK PADA SISWA DI SMAN 1 PALMATAK - Elvita Nora Susana; Malahayati Rusli Bintang; Salsabila Dewari (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2026)
ABSTRACT Background: Laryngeal cancer is one of the upper respiratory tract malignancies strongly associated with smoking habits. Adolescents are considered a high-risk group because they are easily influenced by peers and generally have low levels of health literacy. Limited understanding of the risks of laryngeal cancer may affect adolescents’ attitudes and smoking behaviors. Objective: This study aimed to determine the relationship between the level of knowledge about laryngeal cancer and attitudes as well as smoking behavior among students of SMA Negeri 1 Palmatak. Methods: This study used a descriptive analytic design with a cross-sectional approach. The study population consisted of all students of SMA Negeri 1 Palmatak, with 140 respondents selected using a total sampling technique. Data were collected using a structured questionnaire. Data analysis was performed using Spearman’s rho test to examine the relationship between knowledge and attitude, and the Lambda (λ) test to analyze the relationship between knowledge and smoking behavior. Results: Most students had good knowledge (53.6%), showed a positive attitude toward smoking prevention (65.7%), and were non-smokers (62.1%). The analysis showed a significant relationship between knowledge and attitude toward smoking (r = 0.730; p < 0.001). In addition, the Lambda test indicated a strong association between knowledge and smoking behavior (λ = 0.698; p < 0.001). Conclusion: The results revealed a strong and statistically significant association between knowledge of laryngeal cancer and smoking-related attitudes and behaviors among students at SMA Negeri 1 Palmatak. Keywords: Knowledge, Laryngeal Cancer, Attitude, Smoking Behavior, Adolescents